P 98 Emotional arousal evoked by novel sounds is reflected in increased sympathetic activation – developmental effects, pupil dilation, and the P3a component. Issue 10 (October 2017) - Wetzel, N.; Schröger, E.; Buttelmann, D.; Schieler, A.; Widmann, A.
Abstract : Unexpected novel sounds occurring outside the current focus of attention can involuntarily capture attention. The underlying mechanisms can be investigated measuring the pupil dilation response (PDR) and the event-related potential (ERP) component P3a in the EEG (for review see, Wetzel and Schröger, 2014 ). Emotional sounds have a high relevance and might cause a stronger orienting of attention and evaluation for novelty than neutral sounds. Emotional arousal was previously associated with increased sympathetic activity (Bradley et al., 2008 ). In a first study we tested a current theory on the generation of the P3a that suggests that P3a and the autonomic response reflect the co-activation of the locus coeruleus-norepinephrine system and the peripheral sympathetic nervous system (SNS;Nieuwenhuis et al., 2011 ). We measured the PDR and the P3a while presenting emotional and neutral novel sounds within a sequence of repeated standard sounds (auditory oddball paradigm). In order to dissociate the contributions of the muscles controlled by the parasympathetic and sympathetic nervous system to the PDR we varied the lighting conditions. Results revealed that only the contribution of sympathetic activation but not parasympathetic inhibition as well as the P3a amplitude were enhanced in response to emotional compared to neutral novel sounds supporting the introduced hypothesis. In a second pupillometry study we presented an auditory oddball paradigm including emotional and other distractor sounds to infants and an adult control group. Distractor sounds elicited a biphasic PDR in both age groups. A principal component analysis revealed a significant increase from the faster component (associated with the parasympathetic inhibition) to the slower component (associated with the sympathetic activation) of the PDR in response to emotional distractor sounds in infants only. Results indicate that infants are more sensitive to emotionally high arousing novel sounds than adults. In sum, our results indicate that (1) emotional arousal is reflected in increased sympathetic activation, (2) the P3a is associated with the SNS activation, and (3) there are developmental differences in the response to emotionally arousing distractor sounds. Importantly, the successful dissociation between the parasympathetic and sympathetic contribution to the PDR enables us to study processes of attention and cognition in particular in children, patients, or other populations where pupil diameter can be measured significantly easier than other psychophysiological parameters.